KADAR LOGAM BERAT (PB, CD, HG, DAN AS) PADA SUMBER AIR MINUM ISI ULANG (AMIU) DI KOTA MANADO - Kabuhung, Anselmus; Sembel, D.T.; Rumengan, I.F.M. (Pascasarjana Unsrat, 2013)
The research data was obtained from direct observations and interviews with the manager of the depots, while the levels of some heavy metals (Pb, Cd, Hg, and As) in drinking water sources and recharge derived from the results of laboratory examination and presented in the form of table, graphs and compared with standard appropriate quality standard regulations (Permenkes No.492/Menkes/Per/IV/2010 on Drinking Water quality Requirements and Minister Regulation. 416/Menkes/per/IX/1990 of these Terms and Water quality Monitoring). Metal content of Pb, Cd and Hg in both raw water sources and refilled drinking water did not exceed the set standard quality, while the metal content of As in the water source did not exceed the standards for quality, but there was one depot of refill drinking water which obtained its water from water source had exceeded the drinking water quality standards in excess of 84% of the standard.